Multi‐Dimensional Structure: Electrocatalytic Enhancement of 0D/1D/2D Multidimensional PtCo Alloy@Cobalt Benzoate/Graphene Composite Catalyst for Alcohol Electro‐Oxidation (Adv. Mater. Interfaces 19/2019). Issue 19 (9th October 2019) - Bai, Ping; Tian, Fuli; Wang, Hui; Yang, Ting; Bi, Xi; Chai, Zhanli; Wang, Xiaojing
Abstract : A novel 1D/2D/3D multidimensional catalyst, which is constructed by PtCo alloy nanoparticles, colalt benzoate nanofibers, and graphene layers, exhibited significant electrocatalytic enhancement and durability extension in variety alcohol oxidation. More details can be found in article number 1900946 by Ping Bai, Zhanli Chai, and co‐workers.